Indigenous Knowledge of Shea Processing and Quality Perception of Shea Products in Benin - Honfo, Gbenato Fernande; AKISSOE, H. NOËL; SOUMANOU, MANSOUROU MOHAMED (My University, 2012)
A survey among 246 people belonging to 14 ethnic groups and living in 5 different parklands in Benin revealed different practices to process shea kernels (namely boiling followed sun drying and smoking) and extract shea butter. A relation between parklands, gathering period, and sun-drying conditions was established. Moisture content and appearance of kernels were the selection criteria for users of shea kernels; color was the main characteristic to buy butter. Constraints to be solved are long processing times, lack of milling equipment and high water requirements. Best practices for smoking, sun drying, and roasting operations need to be established for further improvement.
Keywords: karité; Vitellaria paradoxa; shea kernels; shea butter; Otamari; forest products